2013
DOI: 10.1128/aac.00811-12
|View full text |Cite
|
Sign up to set email alerts
|

Candida glabrata Drug:H + Antiporter CgQdr2 Confers Imidazole Drug Resistance, Being Activated by Transcription Factor CgPdr1

Abstract: The widespread emergence of antifungal drug resistance poses a severe clinical problem. Though predicted to play a role in this phenomenon, the drug:H ؉ antiporters (DHA) of the major facilitator superfamily have largely escaped characterization in pathogenic yeasts. This work describes the first DHA from the pathogenic yeast Candida glabrata reported to be involved in antifungal drug resistance, the C. glabrata QDR2 (CgQDR2) gene (ORF CAGL0G08624g). The expression of CgQDR2 in C. glabrata was found to confer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(95 citation statements)
references
References 44 publications
5
89
0
1
Order By: Relevance
“…This is consistent with the characterization of several of these proteins as efflux pumps, despite a role in specific clotrimazole transport had only been described for CgQdr2 (31). The most up-regulated protein in this cluster is CgCdr1, widely characterized as an important ATP-binding cassette transporter.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…This is consistent with the characterization of several of these proteins as efflux pumps, despite a role in specific clotrimazole transport had only been described for CgQdr2 (31). The most up-regulated protein in this cluster is CgCdr1, widely characterized as an important ATP-binding cassette transporter.…”
Section: Resultssupporting
confidence: 67%
“…Interestingly, at least one CgPdr1-binding site is found in the promoter regions of the first four genes, suggesting that the action of CgPdr1 in their expression may be direct. These results are consistent with the characterization of several of these proteins as efflux pumps and of their expression to be dependent on CgPdr1 in response to other chemical stress inducers (30,31,35,37). The expression changes here observed reinforce CgPdr1 as a major pleiotropic drug resistance mediator and highlight its role in mediating the expression of multidrug transporters in response to clotrimazole.…”
Section: Effect Of Cgpdr1 Deletion In the Membrane Proteomewide Changsupporting
confidence: 79%
See 1 more Smart Citation
“…This is similar to the situation in S. cerevisiae, although there are two unique C. glabrata targets, YBT1 and QDR2. QDR2 has been observed by another group to be under the transcriptional control of Pdr1 (28). These data coupled with our ChIP-seq analysis provide arguably the strongest case for an MFS protein-encoding gene regulated by Pdr1.…”
Section: Discussionsupporting
confidence: 49%
“…Up-to-date research has highlighted the important role that complex resistance gene overexpression interactions play in FLC resistance in C. glabrata, and has demonstrated that overexpression of ABC membrane transporter genes is a pivotal FLC resistance mechanism in C. glabrata clinical isolates (Abbes et al, 2013). Although the MFS transporter genes FLR1 and QDR2 in C. glabrata are known to be involved in azole efflux, the expression of FLR1 and QDR2 in C. glabrata was not found to confer resistance to FLC (Chen et al, 2007;Costa et al, 2013). Therefore, the investigation of FLC resistance gene expression did not involve the MFS transporter genes in this work.…”
Section: Discussionmentioning
confidence: 91%